(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
In the centers of teacher training emerges an influential and basic phenomenon in the quality educational praxis, constituted by the perceptions of the learning of its key actors. This affirmation promotes the study of this construct with the purpose of unveiling and updating the essential elements as distinctive for its conceptualization. This study was inserted in the naturalistic paradigm, where the method to process the information and to interpret it in its essence was the phenomenological one. The initial informants were made up of students and professors of the Cognitive Processes Development Course (DPC 0113) of the Miranda Pedagogical Institute José Manuel Siso Martínez de Venezuela in the academic periods 2015-II - 2016-I. Under the principles of theoretical saturation, the 12 final informants were determined. The techniques used to gather information were participant observation, supported by an observation guide and the in-depth interview, based on an interview script. The emerging findings allow us to affirm that the perception about learning in teacher training continually changes along with the cognitive, affective and ethical actions of the subjects that make it up. This phenomenon allows us to construct theoretical approaches that allow us to generate actions for quality teacher training.